Use of diacerein for the treatment of large joint osteoarthritis (A review of literature and the author’s own experience) - Rimma Mikhailovna Balabanova (Современная ревматология)
Osteoarthritis is (OA) is a chronic slowly progressive inflammatory disease, in the pathogenesis of which a large role is assigned to immune disorders: increased synthesis of proinflammatory cytokines (interleukin 1, tumor necrosis factor-α) that activate catabolic processes not only in cartilaginous tissue, but also in subchondral bone and other joint structures. Nonsteroidal anti-inflammatory drugs are recommended to be used as symptom-modifying agents that block the production of prostaglandins. The choice of slowly symptomatic drugs is rather wide. Diacerein is one of them. The author has evaluated the efficacy and safety of diacerein in the treatment of knee and hip OA over a period of 7 years. She also presents her own experience in using the drug.